G160(P) Case series of Pervasive Refusal Syndrome presenting with Chronic Fatigue Syndrome: avoiding the pitfall of a wrong diagnosis. (7th April 2014) - Herberholz, N; Collin, S; McCowat, A; Crawley, E
Abstract : Aim: Children with Pervasive Refusal Syndrome (PRS) present to paediatric services with symptoms of fatigue, low mood and severe functional disability. Little is known about PRS or how to differentiate it from CFS/ME. We investigated differences in presentation between children diagnosed with PRS and those with Chronic Fatigue Syndrome (CFS/ME) in a large paediatric CFS/ME service. Methods: We identified children with PRS by: reviewing the CFS database (assessments 2005–2011). We also asked the CFS/ME specialist service about patients they had assessed who had received the diagnoses. We compared routinely measured assessment data between those with PRS and those with CFS/ME. We retrieved notes from patients with PRS to identify clinical similarities between patients. Results: Seven patients (4 females) received a diagnosis of PRS (mean age 13.5 years). Routinely collected assessment data was available for 6/7 patients (Table 1). Patients with PRS were similar to those with CFS/ME in terms of age, gender, presence of anxiety or depressive symptoms, time to assessment and pain. They were more disabled than CFS patients (mean SF-36 physical function 0 compared to 50, P = 0.02) and had higher levels of fatigue (mean fatigue 8 points higher, p = 0.03). Clinicalfeatures for PRS patients Six patients had impairment in eating (no disordered body image), self-care, social withdrawal and significant reduction in mobility and activity. Five refused treatment and three had communication impairment. All patients described post-exertional fatigue but un-refreshing sleep was only present in four. Pain was experienced by all patients, four described sensory integration difficulties. Six had disrupted sleep pattern and six cognitive impairment (concentration, memory). Conclusions: Clinicians should think about PRS in patients with refusal symptoms affecting, eating, social interaction, self-care, mobility and treatment. Patients have extremely high levels of fatigue and/or disability. Postexertional fatigue and disrupted sleep occur but patients are less likely to have characteristic symptoms of CFS/ME such as unrefreshing sleep. The diagnosis of PRS is important as the treatment is different.